2019
DOI: 10.31557/apjcp.2019.20.1.221
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Key Genes and Pathways for Medulloblastoma as a Therapeutic Target

Abstract: Introduction:One of the major challenges in cancer treatment is the lack of specific and accurate treatment in cancer. Data analysis can help to understand the underlying molecular mechanism that leads to better treatment. Increasing availability and reliability of DNA microarray data leads to increase the use of these data in a variety of cancers. This study aimed at applying and evaluating microarray data analyzing, identification of important pathways and gene network for medulloblastoma patients to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Feng et al investigated poor prognosis-related genes of ovarian cancer by bioinformatics analysis and found that these genes were mainly enriched in the cell cycle pathway (27). It has also been reported that the cell cycle pathway is the key signaling pathway for 8 target therapy of neuroblastomas (28). Zhang et al reported that LncRNA CASC11 promoted the proliferation, migration, and invasion of GC cells in vitro via the cell cycle pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al investigated poor prognosis-related genes of ovarian cancer by bioinformatics analysis and found that these genes were mainly enriched in the cell cycle pathway (27). It has also been reported that the cell cycle pathway is the key signaling pathway for 8 target therapy of neuroblastomas (28). Zhang et al reported that LncRNA CASC11 promoted the proliferation, migration, and invasion of GC cells in vitro via the cell cycle pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, most gene chip data is a mixture of both MB and glioma and does not accurately represent changes in MB, and therefore does not generate satisfactory results. There have been reports of microarray data to find DEGs in medulloblastoma (Shaabanpour Aghamaleki et al, 2019). However, the reliability of the analysis results was controversial due to the heterogeneity of the sample from a single cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…Isochromosome 17q and KCNA1 function as immunohistochemical markers that are seen in group 4 of medulloblastoma [14]. Furthermore, several protein-coding genes mutation and expression modification are seen in medulloblastoma patients that act as medulloblastoma pathogenesis [15]. There are other existing mechanisms that control gene expressions, such as, noncoding RNAs like microRNAs (miRNAs) and lncRNAs, DNA methylation and histone modifications.…”
Section: Introductionmentioning
confidence: 99%